Proceedings of the Ocean Drilling Program, 161 Scientific Results 1999
DOI: 10.2973/odp.proc.sr.161.239.1999
|View full text |Cite
|
Sign up to set email alerts
|

Biostratigraphy and paleoceanography of the Pliocene at Sites 975 (Menorca Rise) and 976 (Alboran Sea) from a quantitative analysis of the planktonic foraminiferal assemblages

Abstract: The Pliocene assemblages of planktonic foraminifers at Sites 975 and 976 were studied quantitatively to obtain data both on the biostratigraphy and on the paleoceanographic conditions prevailing in the western Mediterranean during the Pliocene. Some significant changes in the composition of the assemblages could be used to complement the biochronology of hemipelagic marine sedimentation in the western Mediterranean. Using modern analog techniques, paleoceanographic conditions were assigned to the Pliocene asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…This is generally in agreement with the later work at Site 975 (Serrano et al 1999) that shows conditions similar to present day punctuated several times by subtropical and therefore warmer assemblages. Marine sequences analysed by Spaak (1983) from the islands of Sicily and Crete reveal similar SST conditions, although somewhat reduced seasonality (slightly cooler summer conditions) relative to present day.…”
Section: (G ) Mediterranean Seasupporting
confidence: 81%
“…This is generally in agreement with the later work at Site 975 (Serrano et al 1999) that shows conditions similar to present day punctuated several times by subtropical and therefore warmer assemblages. Marine sequences analysed by Spaak (1983) from the islands of Sicily and Crete reveal similar SST conditions, although somewhat reduced seasonality (slightly cooler summer conditions) relative to present day.…”
Section: (G ) Mediterranean Seasupporting
confidence: 81%
“…The full temperature range over the whole year is between 15°C in February and 23°C in August; average fall and spring SSTs are 18°C and 17°C. Initial stratigraphic and palaeoceanographic work demonstrated the continuity of multiple offset‐drilled hydraulic piston cores that were recovered during ODP Leg 161 at Site 976 [ Zahn et al , ] and revealed high sedimentation rates at the Site of >20 cm/kyr [ Combourieu‐Nebout et al , ; de Kaenel et al , ; Serrano et al , ; von Grafenstein et al , ].…”
Section: Methodsmentioning
confidence: 99%
“…The ODP976 records help to shed light on the so far controversially discussed issue [Carlson, 2008;Bauch et al, 2012;Sánchez-Goñi et al, 2013] if climatic oscillations like the Bølling/Allerød and Younger Dryas that feature prominently during T1 also existed during T2. and revealed high sedimentation rates at the Site of >20 cm/kyr [Combourieu-Nebout et al, 1999;de Kaenel et al, 1999;Serrano et al, 1999;von Grafenstein et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Biostratigraphic events were derived mainly from Lourens et al (2004). Additional datums are adopted from Weaver and Clement (1987), Chaisson and Pearson (1997), Krijgsman et al (2004), Berggren et al (1995), Hilgen (1991), Serrano et al (1999), and Sierro (unpubl. data) ( Fig.…”
Section: Foraminifersmentioning
confidence: 99%